1982
DOI: 10.1073/pnas.79.4.1225
|View full text |Cite
|
Sign up to set email alerts
|

At least two regions of the viral genome determine the oncogenic potential of avian leukosis viruses.

Abstract: Recombinants of oncogenic and nononcogenic avian leukosis viruses were tested for their oncogenic potential in chickens. The results indicate that at least two regions of the viral genome determine the oncogenic potential of these viruses. The first region contains sequences that control viral mRNA synthesis. These sequences determine the potential of a virus to induce a low incidence oflymphomas, carcinomas, chondrosarcomas, fibrosarcomas, and osteopetrosis. The second region lies outside the sequences that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
0

Year Published

1985
1985
1986
1986

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 39 publications
3
76
0
Order By: Relevance
“…In fact, RAV-0 becomes oncogenic when its own U3 region is replaced by that of RSV (Robinson et al, 1982;Tsichlis et al, 1982). Furthermore, it has been demonstrated that the LTR of a tumorigenic retrovirus (RAV-2) gives rise to a 10-fold higher level of env gene transcription than the RAV-0 LTR (Cullen et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, RAV-0 becomes oncogenic when its own U3 region is replaced by that of RSV (Robinson et al, 1982;Tsichlis et al, 1982). Furthermore, it has been demonstrated that the LTR of a tumorigenic retrovirus (RAV-2) gives rise to a 10-fold higher level of env gene transcription than the RAV-0 LTR (Cullen et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Since RAV-0 is an endogenous virus which also has the ability to multiply in avian cells, it might be that the loss of enhancer activity evolved to reduce oncogenicity without losing viability. Robinson et al (1982) and Tsichlis et al (1982) have demonstrated that replacing the U3 region of the RAV-0 LTR with the homologous region of td-RSV restores oncogenicity in vivo. Thus, the U3 region determines the potential of a virus to induce malignant diseases such as lymphomas, carcinomas, chondrosarcomas, fibrosarcomas and osteopetrosis Robinson et al, 1982).…”
Section: Selection Of Enhancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, oncogene activation and neoplastic disease can also follow the chromosomal integration of a nonacute transforming retrovirus near these potentially transforming host genes. The major retroviral sequences necessary for transformation in avian leukosis virus have been localized to the U3 region of retroviral long terminal repeats (LTRs) (21,22,(31)(32)(33). Recent studies with murine nontransforming retroviruses also argue for the importance of the proviral LTR sequences in determining oncogenicity (3,6,15).…”
mentioning
confidence: 99%